IMPLEMENTASI PENGENALAN GENDER TERHADAP ANAK USIA DINI MELALUI KEGIATAN BERMAIN BOMBIX DI KB NANDA CERIA BOCEK KARANGPLOSO MALANG - Ummah, Salimatul (Thufuli, 2021)
This study aimed to describe the implemetation of gender recognition in early childhood through playing Bombix at the Nanda Ceria play group, Bocek, Karangploso, Malang. This research uses a descriptive qualitative approach. Research subjects are early childhood aged 3-4 years, class teacher, and head of institutions. The results of this study indicate that the introduction of gender to early childhood is caaried out playing Bombix activities which are arranged by children according to predesigned themes/sub themes. The results of the implementation of the implementation of gender rocognition in early childhood trough playing Bombix activities are seen when children are assembling Bombix according to their favorite toys that children already know. For example, boys prefer to assemble Bombix into gun masts, robots, fishing rods, while girls prefer to assemble bombix into flower toys, hair clips, and makeup tools. So it can be concluded that playing Bombix is able to provide understanding to children about gender according to their respective gender. Â